Pemerolehan Kalimat Bahasa Indonesia Anak Usia 4;0–5;0 Tahun - Aminah Elvina; Gusdi Sastra; Lindawati Lindawati (Center of Language and Cultural Studies, 2020)
The purpose of this research is to describe the acquisition of Indonesian sentences for children aged 4;0-5;0 years old. Specifically, this study aims to explain the types of sentences used by children aged 4;0-5;0 years based on their syntactic form, the number of clauses, and the completeness of the elements. This research is cross-sectional research by using the observation method. The results of this research are as follow; (1) Based on the syntactic form, children aged 4;0-5;0 years use more declarative and interrogative sentences than imperative and exclamative sentences. From 400 data found 117 declarative sentences, 83 interrogative sentences, 17 imperative sentences, and 12 exclamative sentences; (2) Based on the number of clauses, children aged 4;0-5;0 years use compound sentences more than single sentences. From 400 data found 96 compound sentences and 92 single sentences; (3) Third, seen from the type of sentence based on the completeness of the elements, children aged 4;0-5;0 years old use minor sentences more than major sentences. From 400 data found 107 minor sentences and 92 major sentences. Children aged 4;0-5;0 years old already have full proficiency, are able to produce complex sentences but yet fully understand the rules of their native language, especially in the use of affixes.